Correction: Olteanu et al. Paradoxical Psoriasis Induced by Ustekinumab: A Comprehensive Review and Case Report. Medicina 2024, 60, 106 - Andrei Ovidiu Olteanu; Artsiom Klimko; Ioana Tieranu; Olguta Anca Orzan; Cristian Valentin Toma; Elena Mirela Ionescu; Carmen Monica Preda; Cristian George Tieranu (Medicina)
In the original publication [...]